DNA and RNA Profiling in Human Blood: Methods and Protocols - Bugert, Peter (Humana Press, 2009)
DNA Profiling for Blood Cell Antigens -- PCR-ELISA for High-Throughput Blood Group Genotyping -- Single Base Extension in Multiplex Blood Group Genotyping -- Real-Time PCR Assays for High-Throughput Blood Group Genotyping -- Real-Time PCR Assays for High-Throughput Human Platelet Antigen Typing -- Multiplex ABO Genotyping by Minisequencing -- Multiplex Genotyping for Thrombophilia-Associated SNPs by Universal Bead Arrays -- Pyrosequencing of Toll-Like Receptor Polymorphisms of Functional Relevance -- Multiplex HLA-Typing by Pyrosequencing -- High-Throughput Multiplex HLA-Typing by Ligase Detection Reaction (LDR) and Universal Array (UA) Approach -- Medium- to High-Throughput SNP Genotyping Using VeraCode Microbeads -- The Use of Maternal Plasma for Prenatal RhD Blood Group Genotyping -- RNA Profiling in Blood Cells -- Nanoliter High-Throughput PCR for DNA and RNA Profiling -- RNA Stabilization of Peripheral Blood and Profiling by Bead Chip Analysis -- RNA Profiling in Peripheral Blood Cells by Fluorescent Differential Display PCR -- cDNA Amplification by SMART-PCR and Suppression Subtractive Hybridization (SSH)-PCR -- Transcript Profiling of Human Platelets Using Microarray and Serial Analysis of Gene Expression (SAGE) -- Genome-Wide Platelet RNA Profiling in Clinical Samples -- PCR-Based Amplification of Platelet mRNA Sequences Obtained From Small-Scale Platelet Samples -- MicroRNA Profiling of Megakaryocytes -- Serial Analysis of Gene Expression Adapted for Downsized Extracts (SAGE/SADE) Analysis in Reticulocytes -- Real-Time PCR Analysis for Blood Cell Lineage Specific Markers -- Monitoring the Immune Response Using Real-Time PCR.
Keywords: Analyse; RNS; Blut; Genetischer Fingerabdruck